A rare and severe complication after minimally invasive esophagectomy: First case of a left-sided tension pneumothorax caused by intrathoracic perforation of the herniated transverse colon. Case report and literature review - Mostafa, Karim; Wolf, Carmen; Austrup, Johannes; Franke, Frederike; Jansen, Olav; Both, Marcus; Langguth, Patrick (Frontiers in Gastroenterology, 2023)
Nowadays, a minimally invasive surgical approach is increasingly being chosen to treat distal esophageal tumors. Here, postoperative hiatal herniation has been identified as a potentially severe complication. In such cases, it is still not known whether surgical or conservative treatment is preferable. In this report, we elaborate the case of a 62-year-old male patient who presented at our emergency department with severe chest pain. This patient had undergone minimally invasive esophagectomy with gastric pull-up 2 years prior to this event. Emergency computed tomography revealed a left-sided tension pneumothorax based on transhiatal herniation of the transverse colon causing an intrathoracic closed-loop obstruction with subsequent perforation. Immediate surgical treatment was initiated and the transverse colon could be successfully repositioned and resected. Nevertheless, the patient died due to postoperative septic shock in the setting of fecal peritonitis, mediastinitis, and pleuritis within 48 hours after surgery. We provide a detailed description of this rare case and provide a review of the literature concerning intrathoracic colonic hernations.